A contribution of Bayesian approach to experimental economics (2016)
The main contribution of this work is the discussion about the widespread of the data from the economic experiments. Particularly, in regards with those that research about the discounting rate of the agents, where we suggest using the Dynamic Stochastic General Equilibrium models (DSGE) under a Bayesian approach. Besides, the inclusion of the entrepreneurs in the economic experiments in order to establish which are the long and short discounting rate is also mentioned. In this way, in order to reach what was said before, both a Neoclassic and a Neo Keynesian standard model were used to contrast the parameters robustness. Finally, it is showed that both the short and long term discounting rates after using Bayesian estimation are more consistent with the experiments carried out with entrepreneurs than those with students.